(untitled) (TERRA LATINOAMERICANA, 2025)
In the High Valleys of Mexico, maize (Zea mays L.) is an economically and culturally important crop. However, average grain yield does not meet the increasing demand; therefore, one strategy to enhance productivity is the use of trilinear hybrids in agrosystems where their yield potential can be fully exploited. For these hybrids, it is advisable to define the most suitable genetic conformation to ensure optimal agronomic performance. This study evaluated the ef fect of dif ferent crossing orders on the productivity of ten trilinear maize hybrids. Field experiments were established in Cuautitlán Izcalli (clay loam soil) and Texcoco (sandy loam soil) under a randomized complete block design with three replications. Key agronomic variables were recorded, including grain yield and its components, male and female flowering, and plant height. The results showed significant dif ferences between environments, attributed to contrasting edaphic and climatic conditions. The average grain yield of the hybrids was 5.50 Mg ha-1. Hybrid H5 (L3 × L4 × L9) showed the highest yield (5.85 Mg ha-1), whereas H1 (L1 × L4 × L9) exhibited the lowest yield (4.70 Mg ha-1). In general, crossing order did not significantly af fect grain yield, except in hybrid H7, in which the combination (L4 × L9) × L7 exceeded its reciprocal by 20.7%. Flowering traits and plant height were consistent across most genotypes, with no relevant floral asynchrony observed. These findings indicate that, for most of the evaluated trilinear hybrids, crossing order was not a determinant factor influencing productivity, which facilitates seed production because seed increase can be conducted using any parental combination. In the specific case of H7, parental order does influence performance; therefore, the optimal combination must be defined during seed multiplication.